2014
DOI: 10.2147/ijn.s66785
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative fullerol promotes osteogenesis of human adipose-derived stem cells

Abstract: Antioxidants were implicated as potential reagents to enhance osteogenesis, and nano-fullerenes have been demonstrated to have a great antioxidative capacity by both in vitro and in vivo experiments. In this study, we assessed the impact of a polyhydroxylated fullerene, fullerol, on the osteogenic differentiation of human adipose-derived stem cells (ADSCs). Fullerol was not toxic against human ADSCs at concentrations up to 10 μM. At a concentration of 1 μM, fullerol reduced cellular reactive oxygen species aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 59 publications
(65 reference statements)
1
36
0
Order By: Relevance
“…OCN is a common signal molecule that promotes osteogenesis and bone inducing factors (17). OCN is a common signal molecule to promote osteogenesis of bone inducing factors (18). Therefore, the present study identified that treatment with fullerenol significantly increased the expression of ALP and OCN in D-galactose-induced mice (P<0.05).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…OCN is a common signal molecule that promotes osteogenesis and bone inducing factors (17). OCN is a common signal molecule to promote osteogenesis of bone inducing factors (18). Therefore, the present study identified that treatment with fullerenol significantly increased the expression of ALP and OCN in D-galactose-induced mice (P<0.05).…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, the present study identified that treatment with fullerenol significantly increased the expression of ALP and OCN in D-galactose-induced mice (P<0.05). Yang et al (18) reported that fullerenol promotes osteogenesis of human ADSCs through Runx2, ALP and OCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Our previous study showed that the CNTs can accelerate gap junction formation remarkably via activation of the β1-integrinmediated FAK/ERK/GATA4 pathway. 22 Yang et al 23 found that the 0D fullerol enhances the osteogenesis of human adipose-derived stem cells. Despite these exciting findings, relatively little is known about the molecular mechanism of fullerene-C 60 in proliferation and cardiomyogenic differentiation of MSCs.…”
mentioning
confidence: 99%
“…37 Fullerene-C 60 treatment partially improved the DNA synthesis in cells, resulting in higher cell number and proliferation. 23,38 The MTT assay was conducted to measure cell proliferation and viability following exposure to fullerene-C 60 for 7 days. As shown in Figure 4C, the cells proliferated constantly in all the groups.…”
mentioning
confidence: 99%